Early death and causes of death of people with intellectual disabilities: A systematic review - O'Leary, Lisa; Cooper, Sally‐Ann; Hughes‐McCormack, Laura (Journal of applied research in intellectual disabilities, 2018)
Background: Death of people with intellectual disabilities is considered to be earlier than for the general population. Methods: Databases were searched for key words on intellectual disabilities and death. Strict inclusion/exclusion criteria were used. Information was extracted from selected papers, tabulated and synthesized. Prospero registration number: CRD42015020161. Results: Of 19,111 retrieved articles, 27 met criteria. Death was earlier by 20 years. It has improved in recent decades; however, the same inequality gap with the general population remains. More severe intellectual disabilities, and/or additional comorbidities rendered it shortest. Standardized mortality rates showed a greater inequality for women than men. Respiratory disease and circulatory diseases (with greater congenital and lesser ischaemic disease compared with the general population) were the main causes of death. Cancer was less common, and cancer profile differed from the general population. Some deaths are potentially avoidable. All research is from high-income countries, and cause of death is surprisingly little investigated. Conclusions: Improved health care, including anticipatory care such as health checks, and initiatives addressing most relevant lifestyle behaviours and health risks are indicated.